2005
DOI: 10.1300/j147v29n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Social Support, and Workers' Intentions to Leave Their Jobs in Public Child Welfare

Abstract: The present study examined the relationships among stress, social support, and intention to leave in 418 public child welfare workers. Workers with higher levels of stress were more likely to think about leaving, while those receiving greater social support were less likely. Social support did not buffer the effects of organizational stress, but had some effect in buffering the effects of work-family conflict. Implications for agency administration and future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
120
1
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(147 citation statements)
references
References 40 publications
9
120
1
11
Order By: Relevance
“…For example, Pomaki et al (2010) reported that social support received from coworkers weakens the inverse effect of workload on intention to leave in a group of apprentice teachers, while Kim and Stoner (2008) found a stronger correlation between role stressors and intention to leave in the condition of work-related low social support. However, Nissly et al (2005) could not demonstrate a buffering effect on the relationship between organizational stress and intention to leave for either work-related or out-of-work social support, although they did observe a direct effect for social support received from work-a similar finding to that announced by Gray and Muramatsu (2013). While both of these studies show that receiving social support directly decreases intention to leave, Beehr, Bowling, and Bennett's (2010) study showed a negative impact of social support on intention to leave when the support is received from coworkers.…”
Section: Intention To Leave and Social Support In The Job Stress Processmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Pomaki et al (2010) reported that social support received from coworkers weakens the inverse effect of workload on intention to leave in a group of apprentice teachers, while Kim and Stoner (2008) found a stronger correlation between role stressors and intention to leave in the condition of work-related low social support. However, Nissly et al (2005) could not demonstrate a buffering effect on the relationship between organizational stress and intention to leave for either work-related or out-of-work social support, although they did observe a direct effect for social support received from work-a similar finding to that announced by Gray and Muramatsu (2013). While both of these studies show that receiving social support directly decreases intention to leave, Beehr, Bowling, and Bennett's (2010) study showed a negative impact of social support on intention to leave when the support is received from coworkers.…”
Section: Intention To Leave and Social Support In The Job Stress Processmentioning
confidence: 99%
“…To summarize, a few studies examining the influence of social support on the relationship between job stress and intention to leave have either focused on work overload (Pomaki et al, 2010) or role stressors (Kim & Stoner, 2008) as specific job stressors; but others have investigated global job stress (Gray & Muramatsu, 2013;Nissly et al, 2005). The most striking feature of these studies is that only one has investigated this relationship with respect to various sources of (work and out-of-work) social support (Nissly et al, 2005); others have examined the effects of only work-related social support (supervisor and coworker) (Gray & Muramatsu, 2013;Kim & Stoner, 2008) or only coworker support (Pomaki et al, 2010).…”
Section: Intention To Leave and Social Support In The Job Stress Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Kossek and colleagues (in press) found that work-family specific support from a supervisor more strongly related to WFC than general supervisor support. Furthermore, Nissly et al (2005) found support from significant others to buffer the effect of WFC for public child welfare workers. These findings, along with those of this study, suggest that supervisors should take an active role in providing support to workers and facilitating their ability to obtain support from others.…”
mentioning
confidence: 95%